Clinical considerations at the intersection of hematopoietic cell transplantation and hereditary hematopoietic malignancy - O’Connor, Timothy E.; Shaw, Reid; Madero-Marroquin, Rafael; Roloff, Gregory W. (Frontiers in Oncology, 2023)
In recent years, advances in genetics and the integration of clinical-grade next-generation sequencing (NGS) assays into patient care have facilitated broader recognition of hereditary hematopoietic malignancy (HHM) among clinicians, in addition to the identification and characterization of novel HHM syndromes. Studies on genetic risk distribution within affected families and unique considerations of HHM biology represent exciting areas of translational research. More recently, data are now emerging pertaining to unique aspects of clinical management of malignancies arising in the context of pathogenic germline mutations, with particular emphasis on chemotherapy responsiveness. In this article, we explore considerations surrounding allogeneic transplantation in the context of HHMs. We review pre- and post-transplant patient implications, including genetic testing donor selection and donor-derived malignancies. Additionally, we consider the limited data that exist regarding the use of transplantation in HHMs and safeguards that might be pursued to mitigate transplant-related toxicities.